Living donor right lobe liver transplantation as a treatment for hepatic alveolar echinococcosis: Report of three cases - DEMİRBAŞ, BAHA TOLGA (My University, 2015)
Echinococcus alveolaris is a parasite from tenia family which causes tumor-like lesions in the livers of infected people. If it is not diagnosed in the early stage of the disease, it frequently causes multiple cysts in the liver. The clinical importance of the disease is rapid progression, infiltration into different tissues like a malignant tumor and capacity of creating metastatic masses. The disease could be treated either by surgical resection or liver transplantation. The resection of the cystic disease is the preferred treatment method. In cases where resection is not possible, liver transplantation is the choice of treatment. Here we present three cases which were admitted to the hospital with unresectable hepatic alveolar echinococcosis and treated by liver transplantation successfully. Patients for whom surgical resection is not possible, we recommend liver transplantation as the treatment method.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Surgery Medicine Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Surgery; Gastroenterology; Hepatology; Echinococcus alveolaris; Liver transplantation; SURGICAL-TREATMENT; HYDATID-DISEASE; EXPERIENCE; Echinococcus alveolaris; Liver transplantation.